2020
DOI: 10.3390/microorganisms8020224
|View full text |Cite
|
Sign up to set email alerts
|

Host Innate Immune Response of Geese Infected with Clade 2.3.4.4 H5N6 Highly Pathogenic Avian Influenza Viruses

Abstract: Since 2014, highly pathogenic avian influenza (HPAI) H5N6 viruses have circulated in waterfowls and caused human infections in China, posing significant threats to the poultry industry and the public health. However, the genetics, pathogenicity and innate immune response of H5N6 HPAIVs in geese remain largely unknown. In this study, we analyzed the genetic characteristic of the two H5N6 viruses (GS38 and DK09) isolated from apparently healthy domestic goose and duck in live poultry markets (LPMs) of Southern C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…No mutations were found in both H5N6 HPAV strains. However, mutations in S137A, T160A, and S227R have been found in our strain, and studies have shown that these mutations make H5N6 AIV easier to adapt to mammalian hosts 15,16 . In addition, the AH38 H5N6 virus had the characteristic NA stalk deletion, although no amino acid substitution associated with resistance to NA inhibitors was observed.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…No mutations were found in both H5N6 HPAV strains. However, mutations in S137A, T160A, and S227R have been found in our strain, and studies have shown that these mutations make H5N6 AIV easier to adapt to mammalian hosts 15,16 . In addition, the AH38 H5N6 virus had the characteristic NA stalk deletion, although no amino acid substitution associated with resistance to NA inhibitors was observed.…”
Section: Resultsmentioning
confidence: 63%
“…However, mutations in S137A, T160A, and S227R have been found in our strain, and studies have shown that these mutations make H5N6 AIV easier to adapt to mammalian hosts. 15 , 16 In addition, the AH38 H5N6 virus had the characteristic NA stalk deletion, although no amino acid substitution associated with resistance to NA inhibitors was observed. The K389R, V598T mutations in PB2 protein and the N409S mutation in PA protein, which had been reported to enhance growth capacity in human and mammalian systems, were observed in the AH38 virus.…”
Section: Resultsmentioning
confidence: 99%
“…Viral RNA was extracted from the allantoic fluid using the RNA extraction kit (Vazyme, China) and reverse transcribed using reverse transcriptase (M-MLV; Vazyme). Eight AIV genes were amplified using universal primers ( Wu et al, 2020 ). Purification of polymerase chain reaction products was accomplished using the DNA purification kit (ThermoFisher Scientific, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Significant upregulation of MDA5 and LGP2 have been observed in the lung tissues of Muscovy ducks infected with HPAI H5N1 infection [39,40]. In ducks, both MDA5 and LGP2 activate IRF-7-dependent signaling pathway and induce interferons (IFNs) as well as interferon-stimulated genes (ISGs) production, both of which mediate the antiviral and pro-inflammatory responses during HPAI H5N1 virus infection [8,[39][40][41][42][43][44]. The tripartite motif (TRIM) family of proteins, tripartite motif 25 (TRIM25) and ubiquitin carboxyl-terminal hydrolase 15 (USP15) were expressed in the duck lung tissues (Figure 6).…”
Section: Rig-i-like Receptors Signaling Pathwaymentioning
confidence: 99%